Comparison of Arsenic Speciation Techniques: Focus on Chemical and Electrochemical Methods - Mancilla Gamboa, Juan Claudio; Medalla, C.A.; Bernal, Jorge (Journal of the Chilean Chemical Society, 2025)
Traditional chemical methods, such as HPLC and AAS, are sensitive and selective for arsenic speciation but require complex sample preparation and are costly. In contrast, electrochemical methods, like voltammetry, offer a faster, more sensitive, and cost-effective analysis with a simpler sample preparation, highlighting their sample size and portability. The choice between both approaches depends on the specific needs of the analysis and the available resources.